Striking the Balance: Philippine Rice Policy between Farmers’ Livelihoods, Consumer Welfare, and National Self-Sufficiency - Mirzabaev, Alisher; Zwinger, Jeremy (International Rice Research Institute, 2025)
• The Philippines imposed a 60-day rice import suspension (Sept–Oct 2025) through Executive Order (EO) No. 93 to protect local farmers by allowing the domestic market to absorb the supply from the ongoing harvest season, after unmilled rice prices collapsed to ₱16– ₱18/kg by July 2025 while retail milled rice stayed above ₱40/kg. What will be the effects internally and externally?